Global imbalances and the lessons of Bretton Woods - Eichengreen, Barry J. (Cambridge, Mass. : MIT Press, 2007)
"In Global Imbalances and the Lessons of Bretton Woods, Barry Eichengreen takes issue with the argument that today's international financial system is largely analogous to the Bretton Woods system of the period 1958 to 1973. Then, as now, it has been argued, the United States ran balance of payment deficits, provided international reserves to other countries, and acted as export market of last resort for the rest of the world. Then, as now, the story continues, other countries were reluctant to revalue their currencies for fear of seeing their export-led growth slow and suffering capital losses on their foreign reserves. Eichengreen argues in response that the power of historical analogy lies not just in finding parallels but in highlighting differences, and indeed he finds important differences in the structure of the world economy today."--BOOK JACKET.
1. Global imbalances and the lessons of Bretton Woods -- 2. The anatomy of the gold pool -- 3. How to exit a currency peg : Japan and the end of the Bretton Woods system -- 4. Sterling's past, dollar's future.
Includes bibliographical references and index.
Also available in electronic form.
Keywords: International finance